2014
DOI: 10.1021/ac5012014
|View full text |Cite
|
Sign up to set email alerts
|

Molybdenum Disulfide Quantum Dots as a Photoluminescence Sensing Platform for 2,4,6-Trinitrophenol Detection

Abstract: Transition metal chalcogenides, especially molybdenum disulfide (MoS2), have recently attracted wide attention from researchers as graphene-analogous materials. However, until now, little literature has reported the synthesis of photoluminescent MoS2 materials and their applications in analytical chemistry. We herein presented a facile bottom-up hydrothermal route for the synthesis of photoluminescent MoS2 quantum dots (QDs) by using sodium molybdate and cysteine as precursors. The prepared MoS2 QDs were chara… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

19
264
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 387 publications
(284 citation statements)
references
References 56 publications
19
264
1
Order By: Relevance
“…These materials are generally inorganic substances similar to graphite; particularly, they are substances, which are layered materials of ultrathin nanosheets of transition metal dichalcogenides (TMDCs) with strong in-plane bonding and weak out-of-plane interactions. Such structures facilitate exfoliation into two-dimensional layers of single unit cell thickness, which has been widely used in a many applications including solid lubricants, catalysts, batteries, various nanoelectronic and energy storage devices [4][5][6][7]. To date, a number of methods have been developed to prepare TMDC nano-sheets, -tubes and -particles.…”
Section: Introductionmentioning
confidence: 99%
“…These materials are generally inorganic substances similar to graphite; particularly, they are substances, which are layered materials of ultrathin nanosheets of transition metal dichalcogenides (TMDCs) with strong in-plane bonding and weak out-of-plane interactions. Such structures facilitate exfoliation into two-dimensional layers of single unit cell thickness, which has been widely used in a many applications including solid lubricants, catalysts, batteries, various nanoelectronic and energy storage devices [4][5][6][7]. To date, a number of methods have been developed to prepare TMDC nano-sheets, -tubes and -particles.…”
Section: Introductionmentioning
confidence: 99%
“…The QY of MoS 2 quantum dots is reported from 2.6% to 4.84% (Wu et al, 2015;Wang and Ni, 2014) and the QY of WS 2 quantum dots is reported from 1.8% to 4% Yan et al, 2016). The MoS 2 and WS 2 quantum dots also shows excitation-dependent emission.…”
Section: Comparison Of Graphene and Graphene-like 2d Materails As Donorsmentioning
confidence: 93%
“…A linear detection range from 0.5 to 60 ng mL -1 was achieved with a limit of detection of 0.2 ng mL -1 for PSA detection. Jia et al used aptamer loaded MoS 2 nanoplates as nanoprobes for intracellular ATP detection and photodynamic therapy (PDT) via ATP-mediated controllable release of singlet oxygen(Jia et al, 2015).MoS 2 quantum dots are emerging 2D nanomaterial photoluminescent probes which have been synthesized with strong photoluminescence, high quantum yield and good biocompatibility(Dai et al, 2015;Wang et al, 2014;Wu et al, 2015).Wang et al. used MoS 2 QDs as photoluminescent probes to construct a photoluminescence (PL) quenching sensor for detection of 2,4,6-trinitrophenol (TNP).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Micro-and nanoscaled transition-metal chalcogenides (TMCs) have attracted much attention because of their unique chemical and physical properties, which allow for widespread applications in energy devices, [1][2][3] sensors, [4,5] thermoelectric devices, [6,7] and memory devices. [8,9] Among the various TMCs, copper selenides (Cu x Se, x = 1-2) are very important semiconductors and exist in a wide range of compositions (CuSe, Cu 2 Se, CuSe 2 , Cu 3 Se 2 , Cu 2-x Se etc.)…”
Section: Introductionmentioning
confidence: 99%